POTENCIAL DE UTILIZAÇÃO DE ESPÉCIES ARBÓREAS PARA PROTEÇÃO SOLAR DE EDIFÍCIOS - Brandão, Jamile Brum; Lourenço, Willian Magalhães de; Santos, Joaquim César Pizzutti dos (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The present work aims to evaluate the potential of reducing the energy consumption of residential buildings from the use of vegetable solar protection. Initially the basement and theoretical evaluations were carried out on the subject, verifying the influence of the afforestation in the urban environment and observing the correct forms of insertion of different tree species in the cities. A study was carried out by obtaining the Solar Transmission Percentage (PTS) of four distinct trees, studied for a period of twelve months, in all seasons, observing the shading capacity of each species and its formal characteristics. Later internal measurements were performed in an efficient popular residence, in the facade exposed to solar radiation west and through a computer simulation the conditions of energy consumption for cooling and heating were identified, without the use of solar protection and with the individual use of the four species of trees analyzed. The results showed the influence of the trees in the energy performance of the residence and observed the particular behavior of each species in providing shading, it was concluded that all the trees presented significant results in the reduction of energy consumption in the different seasons.